RELEVANSI LULUSAN PERGURUAN TINGGI DALAM PENEMPATAN KERJA - Supriati Supriati; Tri Handayani (Politeknik Negeri Batam, 2018)
This study aims to determine the level of relevance of graduates in work placements and determine the relevance factors of graduates in work placements. This type of research is descriptive exploratory, the variables studied include the level of relevance of graduates is the level of job suitability obtained by graduates of the Business Administration Study Program in work placements can be seen from the population in this study are graduates (alumni) from the Business Administration Study Program totaling 369 people while the sample was taken in a proportional random sampling that the samples were taken randomly with a sample of 201 people. The questionnaire method is used to reveal data regarding competence, relevance and type of graduate work. The results in this study are the level of relevance of college graduates in work placements obtained 67.2% percentage related to the field of administration and management and 32.8% non administration and management. This proves that the relevance of college graduates in this case is the Bengkalis State Polytechnic in particular the Business Administration Study Program is already relevant (relevant) with this work placement seen from the job description (job description) in accordance with the fields of administration and management. The relevance factors of graduates with work placements are factors of job profile, competency and education level factors.